The geographical sciences during 1986-2015 : from the classics to the frontiers - Leng, Shuying (Springer, 2016)
In four chapters and an introduction, this book systematically helps readers understand the development of the Geographical Sciences both in China and in the world during the past 30 years. Through data analysis of methodologies including CiteSpace, TDA, qualitative analysis, questionnaires, data mining and mathematical statistics, the book explains the evolution of research topics and their driving factors in the Geographical Sciences and its four branches, namely Physical Geography, Human Geography, Geographical Information Science and Environmental Geography. It also identifies the role of the Geographical Sciences in the analysis of strategic issues such as global change and terrestrial ecosystems, terrestrial water cycle and water resources, land change, global cryosphere evolution and land surface processes on the Tibetan Plateau, economic globalization and local responses, regional sustainable development, remote sensing modelling and parameter inversion, spatial analysis and simulation, and tempo-spatial processes and modelling of environmental pollutants. It then discusses research development and inadequacy of Chinese Geographical Sciences in the above-mentioned topics, as well as in the fields including Geomorphology and Quaternary environmental change, Ecohydrology, ecosystem services, the urbanization process and mechanism, medical and health geography, international rivers and transboundary environment and resources, detection and attribution of changes in land surface sensitive components, and uncertainty of spatial information and spatial analysis. It shows that the NSFC has driven the development in all these topics and fields. In addition, the book summarises trends of the Geographical Sciences in China and the research level in major countries of the world through an overview of geographical education in colleges and universities, the analysis of publications, citations and author networks of SCI/SSCI and CSCD indexed articles, and the description of Sino-USA, Sino-UK and Sino-German cooperation. This book serves as an important reference to anyone interested in geographical sciences and related fields.
"Translation from the Chinese language edition."
Keywords: Geography -- China.; Geography -- China -- History.; China.; elektronické knihy; electronic books